The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1371/journal.pone.0059738
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Patients’ EMS Use Related to Severity in Tokyo: A Population-Based Observational Study

Abstract: IntroductionFew studies are available on the clinical characteristics of patients using emergency medical transports in Japan. In this study, we aimed to investigate reasons for emergency medical transports and their relation to clinical severity.MethodsWe conducted a 3-year population-based observational study of patients transported by ambulance to emergency departments (ED) in the capital of Japan, Tokyo, which has a population of about 13 million. Demographic data, reasons for transport, and the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…that respondents probably check "pain" less frequently if it is in the lower third of the list of possible complaints. However, pain was also the most common or a comparably frequent complaint in other countries (like Japan [30] and USA [31,32]). So far, the translated, extended NAIK seems feasible for questioning patients if complaints "dizziness" and "amnesia" are added.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…that respondents probably check "pain" less frequently if it is in the lower third of the list of possible complaints. However, pain was also the most common or a comparably frequent complaint in other countries (like Japan [30] and USA [31,32]). So far, the translated, extended NAIK seems feasible for questioning patients if complaints "dizziness" and "amnesia" are added.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, majority of the cases in health care are not time sensitive or critical. Abe et al (2013) illustrated this with the analysis of ambulance use by the Tokyo region’s inhabitants to its emergency departments. As national health insurance ensures free use of ambulances to its citizens in the case of an emergency, ambulance services are typically widely used.…”
Section: Literature Review: Earlier Simulation Studies From Hospitalsmentioning
confidence: 99%
“…As national health insurance ensures free use of ambulances to its citizens in the case of an emergency, ambulance services are typically widely used. With the availability of three years of data, Abe et al (2013) estimated that severity of injuries was low in 60 per cent out of all ambulance transports, and in turn severe (including critical and death) only in very few (8 per cent of transported patients). In comparison, Brazilian ambulance simulation study (Pinto et al , 2015) showed from real-life data that less than half of ambulance callers (patients) were evaluated to need this acute service.…”
Section: Literature Review: Earlier Simulation Studies From Hospitalsmentioning
confidence: 99%